1976
DOI: 10.1111/j.1365-2141.1976.tb03608.x
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity of Erythrocyte Antigen Distribution in Human Normal Phenotypes: an Immunoelectron Microscopy Study

Abstract: Summary. A and A1 antigen were detected on human blood erythrocytes by immunoelectron microscopy using peroxidase‐conjugated antibodies. Cells were obtained from various normal A subgroups, including rare weak A phenotypes and infant (cord blood) samples. Erythrocytes were fixed prior to incubation with specific reagents. The detection of surface antigens was carried out by an indirect method involving anti‐A and anti‐A1 antibodies and conjugated anti‐immunoglobulin antibodies. The surface labelling was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…26,27 The mechanisms are unclear but are perhaps due to the weaker blood groups being associated with a different sequence in the upstream region. It has recently been shown that an upstream repeat element of the ABO gene, which varies in copy number according to the allele, has enhancing ability.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The mechanisms are unclear but are perhaps due to the weaker blood groups being associated with a different sequence in the upstream region. It has recently been shown that an upstream repeat element of the ABO gene, which varies in copy number according to the allele, has enhancing ability.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we were cautious to avoid agglutination, RBC gates were drawn very tightly, based on side scatter/forward scatter to exclude clumped cells. The number of group O cells staining with lectin was always less than 0.5%; however, the number of group A 1 cells that did not stain with the lectin varied from 0% to 8% (because it was not possible to add excess lectin to ensure binding to all cells and because of differential expression of A 1 antigen 16 ). The small number of recipient A 1 cells that failed to bind lectin was not considered significant for our study because lectin binding was used only to positively identify group A 1 cells and to exclude group O cells.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…This was not correlated with either homo-or heterozygosity for the X chromosome, or with differences in maturity of peripheral blood granulocytes. The phe nomenon shows some analogy with the het erogeneous distribution of the A antigen over normal A erythrocytes [15]. The in teresting possibility that NBj is specific for a subpopulation of granulocytes must be further studied.…”
Section: Discussionmentioning
confidence: 99%